2011
DOI: 10.1074/jbc.m111.289868
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptome of a Human Polar Body Accurately Reflects Its Sibling Oocyte

Abstract: Background: Clinicians need additional metrics for predicting quality of human oocytes for IVF procedures. Results: Human polar bodies reflect the oocyte transcript profile. Conclusion: Quantitation of polar body mRNAs could allow for both oocyte ranking and embryo preferences in IVF applications. Significance: The transcriptome of a polar body has never been reported in any organism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 23 publications
3
49
0
Order By: Relevance
“…They analyzed over 12,700 unique mRNAs and miRNAs from oocyte samples and compared them with 5,431 mRNAs recovered from the sibling PBs. Their results demonstrated that detection and quantification of mRNA in human PBs is possible and that the human PB mRNA transcriptome reflects that of its sibling MII oocyte [9]. This work and our data demonstrated that PB 1 mRNA is being considered as a proxy for the oocyte [29].…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…They analyzed over 12,700 unique mRNAs and miRNAs from oocyte samples and compared them with 5,431 mRNAs recovered from the sibling PBs. Their results demonstrated that detection and quantification of mRNA in human PBs is possible and that the human PB mRNA transcriptome reflects that of its sibling MII oocyte [9]. This work and our data demonstrated that PB 1 mRNA is being considered as a proxy for the oocyte [29].…”
Section: Discussionsupporting
confidence: 65%
“…The polar body (PB) is a cell created by asymmetric division of the oocyte at the time of meiosis and produces a readily accessible test source of genomic material that can be sampled as a proxy for the "sibling" oocyte for diagnostic purposes. Reich et al demonstrated that the transcriptome of a human PB accurately reflects its sibling oocyte [8,9]. The ability to quantify mRNA in individual cells-as small as a single PBopens up the possibility that we can detect and compare individual differences in gene expression in the PB without harming the oocyte.…”
mentioning
confidence: 99%
“…Unfortunately, this type of assessment cannot determine the expression levels of essential genes, nor can it consistently predict the developmental potential of the egg (Rienzi et al, 2011;Wang and Sun, 2007). Recent work from Reich et al (2011) suggests that this hurdle can be overcome by biopsy of the first polar body followed by single-cell transcriptomics to determine the expression of genes known to be crucial for oogenesis. As gene expression in the polar body closely reflects expression in the oocyte from which it derived, the polar body can act as a proxy when choosing oocytes for ART.…”
Section: Understanding Reproductive Senescence In Womenmentioning
confidence: 99%
“…Although embryo morphology has been correlated with implantation potential [6], selecting embryos with the appropriate morphological appearance alone is not sufficient to guarantee embryo viability and improve the chances of pregnancy. Several methods, such as removing the polar body [34] and one blastomere from the embryo on the third day of culture [28], were proposed to evaluate oocyte and embryo development, although it is not known what impact these techniques have on embryonic development. Therefore, new non-invasive approaches in oocyte and embryo metabolomics appear to be an alternative for gamete selection and have been proposed for assessing the potential of oocytes and embryos using embryo culture media, follicular fluid and cells [6].…”
Section: Introductionmentioning
confidence: 99%